Problematic smartphone usage and inadequate mental health literacy potentially increase the risks of depression, anxiety, and their comorbidity in Chinese college students: A longitudinal study - Changru Wang; Jie Hu; Yi Zhou; Linlin Jiang; Jing Chen; Jingjing Xi; Jun Fang; Shichen Zhang (Journal of Affective Disorders Reports)
Background: Problematic smartphone usage (PSU) and mental health literacy (MHL) are potential factors to psychological problems, but interactive and mediate effects in this association remains unclear. This study aimed to examine whether MHL mediate associations of PSU with depression, anxiety, and their comorbidity, and the extent of interaction of PSU and MHL with psychological problems in Chinese college students. Methods: Pooled longitudinal data of 6879 participants was collected between November 2019 and June 2020 to assess the MHL, PSU, depression, and anxiety of college students in Anhui province, China. Mediation analyses and multiple logistic regression models were conducted to explore potential associations. Results: PSU was significantly was positively correlated with depression, anxiety, and their comorbidity, and this association mediated by MHL with the mediation ratio of 4.29 %, 5.86 % and 5.00 %, respectively. Furthermore, students with PSU and inadequate MHL had the highest risk of depression (RR = 4.041, 95 % CI: 3.132–5.214), anxiety (RR = 2.759, 95 % CI: 1.954–3.894), and their comorbidity (RR = 3.805, 95 % CI: 2.592–5.584). Limitations: Retrospective design may introduce recall bias. Conclusions: These findings underscore the vulnerability of individuals with PSU and inadequate MHL to longitudinal risks of experiencing depression, anxiety, and their comorbidity. And MHL mediating the association between PSU and psychological problems. In light of these results, interventions aimed at reducing the incidence and progression of mental health issues among college students should prioritize strategies for decreasing smartphone usage and enhancing MHL.